Pemanfaatan Platform Digital Dalam Program Beasiswa Seni dan Budaya Indonesia Sebagai Bentuk Diplomasi Budaya - Yuliana, Adelia; Djie, Bryan Storm Feryan; Wulandari, Diah Ayu; Sheila, Eirene Eva Marta; Nugroho, Andriyanto Adhi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The existence of the Indonesian Arts and Culture Scholarship Program is expected to expand diplomatic relations between Indonesia and other countries further and make Indonesian culture increasingly recognized and acknowledged. This article aims to discover the role of the Indonesian Arts and Culture Scholarship Program in expanding Indonesian Cultural Diplomacy and the effectiveness of digital platforms in supporting this scholarship program. The method used is a literature study that reviews the results of previous journals relevant to the topic discussed and is complemented by analysis results from internet sites. Participants who have completed arts and culture training will become friends of Indonesian and Indonesian Ambassadors tasked with introducing the arts and culture they have studied to their respective countries. Through the Instagram account @iacs_kemlu, the Ministry of Foreign Affairs can transparently and quickly disseminate information to the public regarding the various activities carried out by the awardees and the positive impacts of the scholarship program. By utilizing digital platforms such as Instagram and TikTok, the government can expand the reach of promoting Indonesian culture to all social media users.